Architecture of Brazil 1900-1990 - Segawa, Hugo (Springer New York : Imprint: Springer, 2013)
Architecture of Brazil: 1900-1990 examines the processes that underpin modern Brazilian architecture under various influences and characterizes different understandings of modernity, evident in the chapter topics of this book. Accordingly, the author does not give overall preference to particular architects nor works, with the exception of a few specific works and architects, including Warchavchik, Niemeyer, Lucio Costa, and Vilanova Artigas. In summary, this book: Meticulously examines the controversies, achievements, and failures in constructing spaces, buildings, and cities in a dynamic country Gives a broad view of Brazilian architecture in the twentieth century Proposes a reinterpretation of the varied approaches of the modern movement up to the Second World War Analyzes ideological impacts of important Brazilian architects including Oscar Niemeyer, Lucio Costa and Vilanova Artigas Discusses work of expatriate architects in Brazil Features over 140 illustrations In Architecture of Brazil: 1900-1990, Segawa brings to the reader an understanding of this important period of architectural history based on his emphasis on processes, allowing the reader to see in-context the leading figures and achievements.